Attitude reactionless and vibration control in space flexible robot grasping operation. (26th December 2018) - Wei, Cheng; Gu, Haiyu; Liu, Yuqiang; Zhao, Yang
When a space flexible robot captures a floating target, the manipulator vibration and the impact reacting onto the base attitude are the key issues which may cause critical safety problems. In this investigation, the attitude reactionless control and the vibration suppression are considered in the meantime to reduce the risk in grasping operation. The dynamic models of the space flexible robot and the target are established, and then the Dynamic Grasping Area is introduced to describe the contact procedure of the capture device grasping target. Even though the flexible vibration of the manipulator can be easily suppressed by using the conventional joint active damping control, the reaction impact to the base attitude is serious and unacceptable. The simulation results indicate that, by using the optimal control for the vibration suppression in the attitude reaction null space, the vibration of the manipulator could be alleviated significantly and the base attitude is also almost undisturbed in the meantime during the whole grasping procedure.